Obstinate leg ulceration secondary to prolidase deficiency, treated with 5% topical proline. (1st February 2022) - Cathcart, Charles; Hanley, Tessa; Gossan, Nicole; Anderson, Emily; Thompson, Ben
Abstract : Prolidase deficiency is a rare cause of chronic ulceration with less than 100 reported cases in the literature. This article highlights to clinicians the features of this uncommon genodermatosis, the challenge of diagnosis, and treatment options.